2021
DOI: 10.1002/jcb.30140
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of BAG3‐HSP70 with the proposed cancer therapeutic JG‐98 is toxic for cardiomyocytes

Abstract: The co-chaperone Bcl2-associated athanogene-3 (BAG3) maintains cellular protein quality control through the regulation of heat shock protein 70 (HSP70). Cancer cells manipulate BAG3-HSP70-regulated pathways for tumor initiation and proliferation, which has led to the development of promising small molecule therapies, such as JG-98, which inhibit the BAG3-HSP70 interaction and mitigate tumor growth. However, it is not known how these broad therapies impact cardiomyocytes, where the BAG3-HSP70 complex is a key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Moreover, while JG98 did not have significant toxicity or effects on sarcomere disruption under the conditions in this study, cardiotoxicity has been observed for JG98 under different conditions. (44)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while JG98 did not have significant toxicity or effects on sarcomere disruption under the conditions in this study, cardiotoxicity has been observed for JG98 under different conditions. (44)…”
Section: Discussionmentioning
confidence: 99%
“…Misfolded proteins are engulfed into nascent autophagosomes to be degraded via the chaperone-assisted selective autophagy CASA formed by the two molecules of HSPB8, the HSP70 cochaperone BAG3 and the HSP70 itself [ 50 ]. A previous study revealed that cancer therapeutic JG-98, which is toxic for cardiomyocytes, inhibits the BAG3–HSP70 interaction and mitigates tumor growth, also reduced autophagy flux and altered the expression of BAG3 and several binding partners involved in BAG3-dependent autophagy, including HSPB8 [ 51 ]. Moreover, BAG3 is critical for the protein turnover of sHSPs via the activation of autophagy in the heart [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these proteins also possess anti-apoptotic activity, which depends on their interactions with either Hsc70/Hsp70 protein or binding to Bcl-2 protein ( Doong et al, 2002 ; Rosati et al, 2011 ). Anticancer drug JG-98 is found to be effective in reducing the cancer cells growth by inhibition of BAG3-HSP70 interaction ( Martin et al, 2022 ). However, this drug induces cardiac toxicity through reduction of BAG3 proteins half-life and reduction of cellular autophagy ( Martin et al, 2022 ).…”
Section: Bag Family and Its Association With Cardiac Diseasementioning
confidence: 99%
“…Anticancer drug JG-98 is found to be effective in reducing the cancer cells growth by inhibition of BAG3-HSP70 interaction ( Martin et al, 2022 ). However, this drug induces cardiac toxicity through reduction of BAG3 proteins half-life and reduction of cellular autophagy ( Martin et al, 2022 ).…”
Section: Bag Family and Its Association With Cardiac Diseasementioning
confidence: 99%